2021
DOI: 10.1002/jcsm.12826
|View full text |Cite
|
Sign up to set email alerts
|

Chronic aryl hydrocarbon receptor activity phenocopies smoking‐induced skeletal muscle impairment

Abstract: Background Chronic obstructive pulmonary disease (COPD) patients exhibit skeletal muscle atrophy, denervation, and reduced mitochondrial oxidative capacity. Whilst chronic tobacco smoke exposure is implicated in COPD muscle impairment, the mechanisms involved are ambiguous. The aryl hydrocarbon receptor (AHR) is a ligand‐activated transcription factor that activates detoxifying pathways with numerous exogenous ligands, including tobacco smoke. Whereas transient AHR activation is adaptive, chronic activation ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 51 publications
5
29
2
Order By: Relevance
“…Other groups have employed smoking mouse models, finding that chronic TS exposure in mice yields atrophy and fiber type shift (Gosker et al, 2009;Basic et al, 2012;Rinaldi et al, 2012;Caron et al, 2013), consistent with the observations in human smokers (Gosker et al, 2007;van den Borst et al, 2011). Smoking mouse studies have also identified a reduced skeletal muscle mitochondrial respiratory capacity (Fukuda et al, 2017;Perez-Rial et al, 2020;Thome et al, 2022), although this is not seen in all studies (Bowen et al, 2017;Decker et al, 2021). Furthermore, we recently showed that chronic TS exposure in mice causes morphological adaptations at the neuromuscular junction, which we propose plays a key role in the motor unit remodeling (fast fiber shift, type grouping), expression of histological markers of denervation (high non-specific esterase activity, high neural cell adhesion molecule [NCAM] expression), and transcriptional indicators of denervation in COPD patient muscle (Kapchinsky et al, 2018).…”
Section: Systemic Mechanisms Of Skeletal Muscle Impairment In Chronic...mentioning
confidence: 54%
See 4 more Smart Citations
“…Other groups have employed smoking mouse models, finding that chronic TS exposure in mice yields atrophy and fiber type shift (Gosker et al, 2009;Basic et al, 2012;Rinaldi et al, 2012;Caron et al, 2013), consistent with the observations in human smokers (Gosker et al, 2007;van den Borst et al, 2011). Smoking mouse studies have also identified a reduced skeletal muscle mitochondrial respiratory capacity (Fukuda et al, 2017;Perez-Rial et al, 2020;Thome et al, 2022), although this is not seen in all studies (Bowen et al, 2017;Decker et al, 2021). Furthermore, we recently showed that chronic TS exposure in mice causes morphological adaptations at the neuromuscular junction, which we propose plays a key role in the motor unit remodeling (fast fiber shift, type grouping), expression of histological markers of denervation (high non-specific esterase activity, high neural cell adhesion molecule [NCAM] expression), and transcriptional indicators of denervation in COPD patient muscle (Kapchinsky et al, 2018).…”
Section: Systemic Mechanisms Of Skeletal Muscle Impairment In Chronic...mentioning
confidence: 54%
“…We then showed that knock-in of a constitutively active mutant of the AHR (demonstrates transcription factor activity without ligand) (Figure 8A) into skeletal muscle cells in vitro recapitulates the muscle atrophy (Figure 8B) and mitochondrial impairment seen with TS condensate (Figures 8C,D). Finally, in mice 12 weeks following intramuscular injection of this constitutively active AHR mutant using an AAV vector revealed muscle atrophy and altered neuromuscular junction morphology that was similar to what was seen with 16 weeks of chronic TS exposure in mice (Thome et al, 2022) (Figure 9). These findings suggest that TSinduced chronic activation of the AHR is likely to be an important contributor to the mitochondrial impairment, muscle atrophy and denervation phenotypes seen in COPD patients, and clearly warrants additional study.…”
Section: Systemic Mechanisms Of Skeletal Muscle Impairment In Chronic...mentioning
confidence: 63%
See 3 more Smart Citations